Analysis of Potable Water Supply Scenarios Using WEAP Software and Applied to the Cities of Moquegua and Ilo - Bohorquez P, Luis M. (2024)
The cities of Moquegua and Ilo are located in a desert close to the Atacama Desert and the supply of water for population use in the current scenario and projected for a 50-year horizon is a concern, that is, to the year 2071; For this reason, the calculations of the current and projected population quantity have been made with a growth rate of 1.6% established by the National Institute of Statistics (INEI). Currently, the demand for water for population use in Moquegua is fully met with contributions from the Pasto Grande dam, but there is a water deficit for Ilo of 43 l/s. In the year 2071 the city of Moquegua will have a population of 204,340 inhabitants and the demand for water for population use will be 0.591 m3/s with an average increase of 7 l/s per year; and the city of Ilo will have a population of 178,722 inhabitants and the demand for water will increase to 0.517 m3/s with an average increase of 5 l/s per year. To analyze the future water supply of the cities of Moquegua and Ilo, a hydrological simulation model has been developed using the WEAP (Water Evaluation and Planning System) software, where the operation of the Pasto Grande dam has been considered, which has a capacity of 200 MMC (Millions of cubic meters), as well as the extraction of water according to the projected water demands, and it is concluded that the water demands for population use of the cities of Moquegua and Ilo can be met with an index of reliability in time and volume of 100%; that is to say, it can be attended in its entirety.